Rapamycin Inhibits Human Laryngotracheal Stenosis–derived Fibroblast Proliferation, Metabolism, and Function in Vitro. (May 2015) - Namba, Daryan R.; Ma, Garret; Samad, Idris; Ding, Dacheng; Pandian, Vinciya; Powell, Jonathan D.; Horton, Maureen R.; Hillel, Alexander T.
Objective: To determine if rapamycin inhibits the growth, function, and metabolism of human laryngotracheal stenosis (LTS)–derived fibroblasts. Study Design: Controlled in vitro study. Setting: Tertiary care hospital in a research university. Subjects and Methods: Fibroblasts isolated from biopsies of 5 patients with laryngotracheal stenosis were cultured. Cell proliferation, histology, gene expression, and cellular metabolism of LTS-derived fibroblasts were assessed in 4 conditions: (1) fibroblast growth medium, (2) fibroblast growth medium with dimethylsulfoxide (DMSO), (3) fibroblast growth medium with 10 −10 M (low-dose) rapamycin dissolved in DMSO, and (4) fibroblast growth medium with 10 −9 M (high-dose) rapamycin dissolved in DMSO. Results: The LTS fibroblast count and DNA concentration were reduced after treatment with high-dose rapamycin compared to DMSO ( P = .0007) and normal ( P = .0007) controls. Collagen I expression decreased after treatment with high-dose rapamycin versus control ( P = .0051) and DMSO ( P = .0093) controls. Maximal respiration decreased to 68.6 pMoles of oxygen/min/10 mg/protein from 96.9 for DMSO ( P = .0002) and 97.0 for normal ( P = .0022) controls. Adenosine triphosphate (ATP) production decreased to 66.8 pMoles from 88.1 for DMSO ( P = .0006) and 83.3 for normal ( P = .0003) controls. Basal respiration decreased to 78.6 pMoles from 108 for DMSO ( P = .0002) and 101 for normal ( P = .0014) controls. Conclusions: Rapamycin demonstrated an anti-fibroblast effect by significantly reducing the proliferation, metabolism, and collagen deposition of human LTS fibroblast in vitro. Rapamycin significantly decreased oxidative phosphorylation of LTS fibroblasts, suggesting at a potential mechanism for the reduced proliferation and differentiation. Furthermore, rapamycin's anti-fibroblast effects indicate a promising adjuvant therapy for the treatment of laryngotracheal stenosis.